ANALYSIS OF WILLINGNESS TO PAY CONTRIBUTIONS IN THE MEMBERSHIP OF THE NATIONAL HEALTH INSURANCE IN REGENCY OF BANYUASIN - Apriani, Maya; Zulkarnaian, Mohammad; Idris, Haerawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
BPJS Kesehatan as the manager of the National Security Program (JKN), can be an appropriate health insurance to reduce the risk of people bearing health costs from their own pocket (out of pocket) in a very large and can lead to poverty. This study aims to analyze the willingness to pay JKN contributions to farmers in Banyuasin Regency in order to identify community groups that need subsidies from the government. This research is an analytical study with cross sectional design. The population of this research is all residents who work as farmers and have not registered as JKN participants with a total sample of 176 people. data analysis used chi square test and logistic regression test. This study found that the willingness to pay JKN contributions of Rp22.028 per person per month. The determinants of willingness to pay contributions in JKN membership are family income, food expenditure, non-essential food expenditure, non-food expenditure, number of family members, history of catastrophic disease, knowledge of contributions, and the ability to pay JKN contributions. The most dominant factor affecting the willingness to pay is non-essential food expenditure. The willingness to pay the JKN dues is still low. The ability to pay contributions is influenced by income, food expenditure, non-essential food expenditure, total non-food expenditure, number of family members, history of catastrophic disease, knowledge of contributions, and the ability to pay JKN contributions.